Food preferences and food choices of eleven and twelve year old children as they relate to their television viewing habits : a thesis submitted in partial fulfilment of requirements for the degree of Master of Science (Nutritional Science) at Massey University - Gordon, Cushla (Massey University, 2004)
The aim of this study was to examine the relationship between children's television viewing habits and their food preferences and food choices. The study was divided into two parts. Part one was an analysis of the frequency and content of food advertisements aired during children's television. Part two involved interviews with children and their parents to examine their eating, television and physical activity habits. From this the relationship between what they were viewing in advertisements and their food preferences and choices could be established. The children, forty in total, were aged eleven or twelve and were chosen from two Auckland Intermediate schools. Comparisons were made between boys and girls. The research showed that New Zealand children, through advertising, are constantly exposed to a variety of foods that fall within a very narrow range. These foods are predominantly individual servings of snacks or pre-prepared, pre-packaged foods that are high in saturated fat and/or sugar and/or salt. These foods are in direct contrast to the dietary recommendations provided by the Ministry of Health (1997) of eating a variety of foods from all the food groups and only eating treat foods now and then. Advertisers within New Zealand are not adhering to the Advertising Codes of Practice, particularly with regard to repetition and duration of advertisements. Thus, self-regulation within this industry does not appear to be effective. From part two of the research it was possible to conclude that television food advertisements do have a significant influence on children. This is through creating a desire in the child to try the foods they have seen advertised and as a result of viewing the advertisement, asking their parents to purchase the food. This effect was most likely to be for the life of the advertisement rather than long-term. Children in the study were watching on average just under two hours of television a day and the more television they were watching, thus the more advertisements they were viewing, the more they wanted to try foods they had seen advertised. More of the children's time was spent viewing television than engaged in formal or informal physical activity. Many were overweight or at risk of overweight, however this was not correlated with television viewing. Overall, television food advertisements influenced children through making the food look appealing and exciting and thus creating a desire to try the food. Children were also influenced by both the qualities of the food, such as taste and appearance, and the people and the environment around them. The research did support the finding in other studies that there is a correlation between children's food likes, dislikes and choices, however it is important to place the influence of advertising in the context of the numerous other influences on children's food choices.
Irregular Pagination Page 63 misnumbered.
Keywords: New Zealand; Television advertising and children; Food preferences; Food habits; Children -- Nutrition